The Effect of Internet of Things (IoT) Towards Social Sciences Student’s Performance - Mohd, Farahwahida; Shamsuddin, Norsila; Ab. Ghani, Puzziawati (International Journal of Engineering and Technology, 2018)
This study is to evaluate the effect of IoT towards social sciences studentâ€™s class performance. This is to measure whether IoT contribute to their performance or not. It is found that e-learning modules are most preferred by the students as compared to blended learning and conventional face-to-face learning environment. E learning was ranked as number 1 most prefer method followed by blended learning and the least preferred is the conventional method that is face-to-face classroom environment. Furthermore, competency in using IT devices such as smart phones, tablet, wi-fi dongle and etc is an advantage in this new era of technology and very significant towards the studentsâ€™ performance (p-value = 0.000). Followed by awareness of the usage of IoT (p-value = 0.011), importance of the devices in contributing good performance (p-value = 0.015) and finally yet importantly usefulness of IoT have significant effect towards performance. All variables are significant at 5% level of significant. Therefore, we can conclude that IoT does give significant effect towards these Social Sciences Studentsâ€™ performance in all of their activities in the university.Â Â